Decoding Speaking Mindsets of Thai Undergraduates using Q-Methodology - Sukklang, Nobphawan; Wilang, Jeffrey (Journal of Studies in the English Language, 2025)
Speaking English remains a persistent challenge in the English as a Foreign Language (EFL) context, specifically in Thailand. This study investigated the perspectives that constitute a speaking language mindset among Thai undergraduate students. This research employed Q-methodology to systematically explore the beliefs of 19 Thai undergraduate students toward foreign language speaking. The participants individually sorted and ranked statements related to foreign language speaking mindset, their responses were analyzed to identify distinct perspectives, including contradictory beliefs. The analysis revealed three primary perspectives: (1) effort and practice as key to improving foreign language speaking ability, (2) self-regulatory tendencies from the appraisal of talent and effort, and (3) discomfort and communication apprehension in classroom settings. The findings suggested that Thai undergraduate students shared a common perspective on effort value, mastery goal orientation, and feedback. The three perspectives pointed out that cultural value, self-perception, and emotional challenges significantly influenced foreign language speaking mindset and language learning experiences. The study highlighted the importance of fostering a supportive learning environment and addressing emotional barriers to enhance students’ foreign language speaking ability in a Thai science-and-technology university. Additionally, the study demonstrated the utility of Q-methodology as a productive tool for uncovering learners’ perspectives in underrepresented educational context.